LEGAL ASPECTS OF CLINICAL TRIALS IN POLAND - Syroka-Marczewska, Katarzyna (Review of European and Comparative Law, 2017)
A clinical trial is each trial conducted in humans to discover or confirm the clinical, pharmacological, including pharmacodynamic, effects of action of one or more investigational medicinal products, or to identify the adverse reactions to one or more investigational medicinal products, or to monitor absorption, distribution, metabolism and excretion of one or more investigational medicinal products, taking into consideration their safety and efficacy. It ought to be remembered that clinical trials may be conducted with the use of medicinal products. Clinical trials must be conducted in a way which is in line with the primary principle that clinical trial participants’ rights, safety, health, and welfare override the interest of science and society.